Devaluation expectations and fundamentals: some new evidence for Ireland 1979-1994 - Walshe, Don; O'Donnell, Mary (Economic & Social Studies, 2001)
This paper uses a Probit model to link economic fundamentals with devaluation expectations for the Irish pound over the period 1979-1994. The estimates relate to both the probability as well as the size of an expected devaluation. The model performs well in predicting the size and timing of actual realignments and estimates of devaluation expectations are consistent with previous estimates based on UIP. While the Maastricht Treaty stipulated the need for exchange rate stability prior to joining EMU, the results here show that economic variables other than those referenced in the Maastricht Treaty can lead to exchange rate instability.
Keywords: Devaluation; Irish pound; European Monetary System; Exchange rates